Palm Oil - Current Status and Updates 2023
DOI: 10.5772/intechopen.106174
|View full text |Cite
|
Sign up to set email alerts
|

Small-Scale Palm Oil Production in Ghana: Practices, Environmental Problems and Potential Mitigating Measures

Abstract: The environmental impact of small-scale palm oil processing mills in Ghana has come under serious questioning, especially the disposal of wastewater generated from their operations. This chapter describes the small-scale palm oil production operations in Ghana to highlight the associated environmental problems arising from the disposal of wastewater and other waste by-products. The chapter further discusses the effluent discharge permitting arrangements and possible modifications to the production practices an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…It is estimated that for every Nigerian household of five, about two liters of palm oil is consumed weekly for cooking [2]. It has also been shown from the 2008 Ghana Demographic and Health Survey that one out of every two households (54%) in the country and four out of five (80%) households in the Centre Region used palm oil in food preparations [3]. Small-scale palm oil processing has been shown to be profitable and can also be a source of employment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is estimated that for every Nigerian household of five, about two liters of palm oil is consumed weekly for cooking [2]. It has also been shown from the 2008 Ghana Demographic and Health Survey that one out of every two households (54%) in the country and four out of five (80%) households in the Centre Region used palm oil in food preparations [3]. Small-scale palm oil processing has been shown to be profitable and can also be a source of employment.…”
Section: Introductionmentioning
confidence: 99%
“…Awere et al [3] observed the need for the treatment of wastewater produced from palm oil processing activities before disposal. They proposed the exploration of treatment technologies that could achieve recovery of resources (e.g., biogas, compost, and earthworm biomass) and fit into the framework of the circular economy.…”
Section: Introductionmentioning
confidence: 99%
“…Small-scale palm oil processing involves the receipt of fresh fruit bunches, splitting, storage, stripping, fermentation, boiling, digestion/pressing, and clarification. Detailed information on the palm oil production processes may be obtained from our earlier publication [10].…”
mentioning
confidence: 99%
“…Table I shows the characteristics of POME from small-scale palm oil processing mills in Ghana and Nigeria as well as industrial-scale mills in Asia. According to numerous research studies, small-scale processing mills typically discharge their POME into the natural environment without any treatment [7,10,[20][21][22]. Improper disposal of POME contaminates the receiving land, aquatic bodies, and air by emitting odour, and contributing to greenhouse gas emissions.…”
mentioning
confidence: 99%